Towards understanding the machining mechanism of the atomic force microscopy tip-based nanomilling process. (March 2021) - Wang, Jiqiang; Yan, Yongda; Li, Zihan; Geng, Yanquan
Abstract: Atomic force microscopy (AFM) tip-based nanofabrication is as a powerful method to machine nanostructures. However, the traditional AFM scratching process suffers from low processing efficiency and a low rate of material removal. Thus, an AFM tip-based nanomilling method was previously proposed to improve the machining efficiency and material removal rate; however, the machining mechanism of the nanomilling process, especially on hard-brittle silicon crystals, is not well understood. In this study, we used an AFM tip-based nanomilling approach to machine nanochannels on single-crystal silicon to investigate the machining mechanism (i.e., the material removal state, undeformed chip thickness, the brittle-to-ductile transition, and subsurface damage). For the first time, we established a theoretical model for tip-based nanomilling with a constant normal load to predict the machined depth. Nanochannels fabricated with a wide range of feed directions, crystal orientations, and tip trajectories were obtained, which provided a reference for machining high-quality nanochannels and an in-depth understanding of the nanomilling of single-crystal silicon. The experimental results demonstrated that we could machine a nanochannel without pile-ups by selecting a specific trajectory with a feed smaller than 4 nm in the 0° direction, a normal load no greater than 120 μN, and a crystal orientation at rotation angles of 135°, 157.5°, or 180°. Moreover, transmission electron microscope analysis of the subsurface of the nanochannel revealed a large number of dislocations, stacking faults, and a layer of amorphous silicon. Our findings are of great significance for obtaining high-quality nanochannels with a predicable machined depth and understanding the nanomilling mechanism of hard-brittle materials. Graphical abstract: Image 1 Highlights: A theoretical model of nanomilling process was established to predict the machined depth of the nanochannel. The undeformed chip thickness, brittle-to-ductile transition and machining mechanism were investigated. The material removal mechanism in brittle regime was analyzed on the basis of the holistic elastic stress field. The sample subsurface damage and phase transformation for nanomilling were investigated by TEM and Raman. The parameters for nanomilling process to fabricate nanochannel without pile-up on silicon were obtained.